P92 Lifestyle interventions for the treatment of overweight/obese adolescents–cochrane review. (2nd September 2017) - Khudairy, LA-K Al; Loveman, EL; Colquitt, JC; Mead, EM; Johnson, RJ; Fraser, HR; Olajide, OJ Joan; Murphy, MM; Velho, RV; O'Malley, CO; Azevedo, LA; Ells, LE; et al.
Abstract : Background: The prevalence of overweight and obese adolescents has increased worldwide, presenting a global public health crisis. This review assessed the efficacy of diet, exercise and behavioural interventions for the treatment of overweight/obesity in adolescents (12–17 years). Methods: A systematic literature search (up to July 2016) with no language restrictions was performed in CENTRAL, MEDLINE, EMBASE, PsycINFO, CINAHL, LILACS, and the trial registers ClinicalTrials.gov and ICTRP Search Portal. Search terms included obesity, diet, exercise and adolescent. References of identified studies and systematic reviews were checked. Authors of included studies were contacted for missed studies. Two reviewers evaluated studies independently at all stages. Eligibility: RCTs that observed participants for ≥six months, overweight/obese (investigator-assessed) adolescents (mean age 12–17 years), interventions with a primary aim to treat overweight/obesity with any form of dietary, exercise and/or behavioural therapy delivered as a single or multi component intervention, any setting and any delivery method. Comparators were no treatment/wait list control, usual care or an alternative concomitant therapy providing it is delivered in the intervention arm. Primary outcomes were changes in BMI/weight measured at baseline and at ≥6 months. Data that could be meta-analysed were expressed as mean differences (MD) with 95% CI otherwise data were reported narratively. Heterogeneity, risk of bias and quality of evidence were assessed. Results: The searches generated 16 106 records (duplicates removed). Title and abstract screen excluded 15 422 records. 736 records were assessed for eligibility. 105 trials were included: 50 ongoing; 11 awaiting classification, 44 qualitative synthesis and 39 quantitative synthesis. This review included 4682 participants. BMI change at the longest follow-up was MD −1.18 (95% CI −1.67 to −0.69); p<0.00001; 2774 participants; 28 trials; low quality evidence. Most studies were multi-disciplinary interventions (BMI MD −1.18, 95% CI −1.75 to −0.61, p<0.0001; 2293 participants; 22 studies), some studies were diet alone (BMI MD −0.62, 95% CI −1.29 to 0.06; p=0.07; 277 participants; 3 studies) or exercise alone interventions (BMI MD −1.73, 95% CI −3.12 to −0.34, p=0.01; 229 participants; 4 studies). Studies undertaken in schools showed a lower effect compered to community and health care settings. Conclusion: Interventions that involve a combination of diet, exercise and behavioural components appear to be an effective treatment option for overweight/obese adolescents. Effects of lifestyle interventions were maintained at 18–24 months follow-up. Results should be interpreted with caution as the evidence was rated as low quality for inconsistency and publication bias.